Origins, Phytochemistry, Pharmacology, Analytical Methods and Safety of Cortex Moutan (Paeonia suffruticosa Andrew): A Systematic Review - Zhiqiang Wang; Chunnian He; Yong Peng; Feihu Chen; Peigen Xiao (Molecules, 2017)
Cortex Moutan (CM), a well-known traditional Chinese medicine, is commonly used for treating various diseases in China and other eastern Asian countries. Recorded in Pharmacopeias of several countries, CM is now drawing increasing attention and under extensive studies in various fields. Phytochemical studies indicate that CM contains many valuable secondary metabolites, such as monoterpene glycosides and phenols. Ample evidence from pharmacological researches suggest that CM has a wide spectrum of activities, such as anti-inflammatory, anti-oxidant, anti-tumor, anti-diabetic, cardiovascular protective, neuroprotective, hepatoprotective effects. Moreover, various analytical methods were established for the quality evaluation and safety control of CM. This review synopsizes updated information concerning the origins, phytochemistry, pharmacology, analytical method and safety of CM, aiming to provide favorable references for modern CM research and application. In conclusion, continuing pharmacological investigations concerning CM should be conducted to unravel its pharmacological mechanisms. Further researches are necessary to obtain comprehensive and applicable analytical approach for quality evaluation and establish harmonized criteria of CM.